A Review on Phytochemical Diversity and Therapeutic Applications of Annona muricata L: Review article (Journal of Pharma Insights and Research, 2026)
Annona muricata L., a prominent member of the Annonaceae family, possesses a diverse repository of bioactive secondary metabolites with documented therapeutic utility across tropical and subtropical regions. Historical applications across various cultures involve the utilization of leaves, bark, roots, and fruit to address a wide spectrum of pathological conditions including parasitic infections, inflammatory disorders, and metabolic diseases. Quantitative analysis of scientific literature spanning four decades reveals a predominant research focus on the plant's antineoplastic properties, followed by significant investigations into its gastroprotective, hypoglycemic, and antimicrobial capabilities. The physiological efficacy of A. muricata originates primarily from Annonaceous acetogenins unique polyethers characterized by tetrahydrofuran rings and gamma-lactone moieties which exhibit potent cytotoxic effects via the inhibition of mitochondrial complex I. The presence of isoquinoline alkaloids, flavonol triglycosides, and essential oils contributes to its multi-targeted pharmacological profile. Clinical and preclinical data substantiate the plant's ability to modulate oxidative stress, induce apoptosis in malignant cells, and inhibit key digestive enzymes associated with type 2 diabetes. While the therapeutic potential is vast, toxicological assessments indicate a narrow safety margin regarding long-term consumption of specific acetogenins, which may correlate with neurodegenerative risks. Consequently, A. muricata is a significant candidate for pharmaceutical development, provided that standardized extraction methods and rigorous safety protocols are established to harness its medicinal benefits effectively